ANÁLISE DA EXCITABILIDADE E CONECTIVIDADE CORTICAL PARA UM SISTEMA DE NEURORREABILITAÇÃO BASEADO EM INTERFACE-CÉREBRO MÁQUINA E MONOCICLO ROBÓTICO - Cardoso, Vivianne Flavia (2021)
CARDOSO V.F. 2021. 110f. Analysis of excitability and connectivity cortical for a neurorehabilitation system based on brain machine interface and robotic monocycle. 2021. 121f. Thesis (doctoral in biotechnology)- Postgraduation Biotechnological Program, U